Diagnostics of concrete plate in bending with ultrasonic waves modulated by low frequency oscillations - Błażej Meronk; Krzysztof Wilde (Budownictwo i Architektura, 2013)
The paper presents the experimental study on the inter-modulation method for the diagnostics of concrete elements. The tests were conducted on a concrete plate subjected to ultrasonic waves and low frequency vibrations. The nonlinear acoustic effects, recorded in the experiments, made it possible to detect the presence of damaged zones. Further studies are necessary to establish the relation between the sidebanes of frequency spectra and the size of the damaged zone.